Application of grey system theory in telecare - Huang, Jui-Chen (Computers in biology and medicine, 2011)
As a superiority to conventional statistical models, grey models require only a limited amount of data to estimate the behaviour of unknown systems. Grey system theory can be used in the effective factor assessment, and used in large samples where data are not available or uncertain whether the data was representative. Therefore, the purpose of this study was to adopt grey system theory to discuss older adult users' opinions on the telecare and its effect on their quality of life. This study surveyed the older adult users of Taiwan as subjects. User perception of the telecare services was collected via face-to-face interview. The grey system theory was used to examine the model. The results showed that the overall living quality has the greatest effect on the perceived effects of the telecare on their quality of life, followed by the acquisition of information, accessibility of medical care services, and safety. This finding may serve as a reference to future studies and it also shows that the grey system theory is a feasible analysis method.